Seroprevalence of toxoplasma gondii and neospora caninum infections in goats from two Argentinean provinces - Gos, Maria Laura (2017)
The aim of this study was to compare the seroprevalence of Toxoplasma gondii and Neospora caninum in goats from two Argentinean provinces raised under different management conditions. A total of 2922 serum samples from adult goats of Córdoba (n=2187) and Buenos Aires provinces (n= 735), Argentina, were assayed by indirect fluorescence antibody test (IFAT, cut-off 1:100) for antibodies to T. gondii and N. caninum. Seroprevalence was 40.8% (CI 39.0%-42.6%) and 5.5% (CI 4.7%-6.4%) for T. gondii and N. caninum, respectively. The seropositivity for both infections was higher in goats from dairy farms, resulting as follows: for T. gondii 32.7% (CI 30.8%-34.8%) in extensive farms and 59.3% (CI 56.1%-62.6%) in dairy farms and for N. caninum 4.1% (CI 3.2%-4.9%) in extensive farms and 8.8% (CI 6.9%-10.7%) in dairy farms. This is the first extensive seroepidemiology investigation for T. gondii and N. caninum in goats in Argentina.